Acoustic method for measuring turbulent state of the atmospheric boundary layer - Sidorov, G.; Sheiko, S.; Shapovalov, S.; Polonska, A.; Dmytrenko, A.I. (Radiotekhnika, 2018)
A model for acoustic waves scattering by turbulent inhomogeneities in the atmospheric boundary layer is proposed and theoretically justified. The requirements for the equipment for experimental studies are given and analysis of the experimental data obtained by an acoustic locator of NURE meeting the requirements is performed. The adequacy of the theoretical model of acoustic waves scattering by turbulent inhomogeneities in the atmosphere and the possibility of classifying the state of turbulence based on the results of measurements of the envelope of echo signals have been proved experimentally.